If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 83 + -5x Reorder the terms: 7 + 6x = 83 + -5x Solving 7 + 6x = 83 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 7 + 6x + 5x = 83 + -5x + 5x Combine like terms: 6x + 5x = 11x 7 + 11x = 83 + -5x + 5x Combine like terms: -5x + 5x = 0 7 + 11x = 83 + 0 7 + 11x = 83 Add '-7' to each side of the equation. 7 + -7 + 11x = 83 + -7 Combine like terms: 7 + -7 = 0 0 + 11x = 83 + -7 11x = 83 + -7 Combine like terms: 83 + -7 = 76 11x = 76 Divide each side by '11'. x = 6.909090909 Simplifying x = 6.909090909
| 13t-7710t=2 | | 4x^2-13x+29=7x+8 | | 5X-2s= | | 2x+26=11x-73 | | 6x^2-11x-35=0 | | -15-2x=9-10x | | 64-2x=9x+20 | | 1+3x=21+x | | 7x-12=-4x | | 5x-30=x+14 | | x^2+4x-37=8 | | 2x+34=11x-47 | | 11x+2=6x+7 | | x^2+4x-37=0 | | 11x-26=62 | | 6x-2=14x-58 | | 14x+30=5x+156 | | 5x+14=94-5x | | 9x-3(2x+1)=0 | | 6x^2-54x+36=0 | | 15x+2=5(3x+4)-8 | | 4x^2+24x-44=0 | | 120-X=.25*80 | | x^2-5x=7 | | 11x+8=7x+24 | | 10m^2=41m+45 | | x^2-12x+9=0 | | -4(p+1)=2(8-2p) | | x^2+16x-1=0 | | x=19-6+x | | x^3-8x^2-5x=-40 | | -7b+2+5b=-3b+7 |